Controle neurovascular e modulação autonômica cardíaca em adolescentes insuficientemente ativos: um estudo exploratório - Silva, Fábio Thiago Maciel da (2021)
Endothelial and autonomic dysfunction has been observed in adolescents with insufficient levels of physical activity, therefore, the aim of this study was to evaluate neurovascular control and cardiac autonomic modulation in insufficiently active adolescents. The research was quantitative, exploratory and correlational. The sample consisted of 26 adolescents (10 boys and 16 girls), with a mean age of 16.4 ± 0.2 years, eutrophic, healthy and classified as insufficiently active. Initially, the adolescents filled out an anamnesis form and the short version of the International Physical Activity Questionnaire (IPAQ). Then, participants performed hemodynamic and anthropometric assessments, blood collections, electrocardiogram and venous occlusion plethysmography. For statistical analysis, a significance level of p<0.05. was considered. Regarding the results, it can be observed that the values of blood flow in the forearm (FSA) and vascular conductance (VC) at baseline were similar to the isometric handgrip exercise maneuver (p=0.145 and p=1,000, respectively), while the mean arterial pressure (MAP) showed significantly higher values during the handgrip (p<0.001). When comparing baseline with hyperemia, significantly lower FSA (p=0.038) and CV (p<0.001) values were observed. Significant inverse correlations were observed between age and VC during handgrip and in reactive hyperemia (p=0.010 and p=0.039, respectively). The results showed positive and significant correlations between the variables FSA (p=0.027), CV (p=0.011) in reactive hyperemia and VC during handgrip (p=0.023), with the number of days of moderate activities. Significant inverse correlations of FSA and VC during handgrip were demonstrated with total cholesterol (p=0.009 and p=0.050, respectively) and LDL-cholesterol with FSA (p=0.009) and with VC (p= 0.036) during the handgrip. Regarding autonomic modulation, values of 1.0 ± 0.0 were observed for the ratio between SDNN/RMSSD and 0.96 ± 0.1 for LF/HF. The results showed positive and significant correlations between the variables SDNN, RMSSD, NN50, pNN50 and the number of days of vigorous activity (p=0.048; p=0.042; p=0.027; p=0.026, respectively). There was a positive and significant correlation with HFms² (p=0.015), inverse with the normalized component LF (p=0.047) and LF/HF (p=0.047) with the number of days of vigorous activity. In the correlations with hemodynamic parameters, it was observed that the normalized component LF presented a significant correlation with SBP (p=0.041), DBP (p=0.006) and MAP (p=0.002). Regarding the normalized HF component, significant 16 correlations were also observed, but in the opposite direction, between SBP (p=0.041), DBP (p=0.006) and MBP (p=0.002). Sympathovagal balance (LF/HF) was significantly correlated with MAP (p=0.005). In the comparisons of the HRV components, according to the categorized groups, there was a significant difference in the HF ms² component, in which group 1 had significantly lower values than groups 2 (p=0.015) and 3 (p=0.021 ). Therefore, it is suggested that insufficiently active adolescents have a compromised vasodilator response and an autonomic vagal predominance, and that higher levels of moderate and vigorous physical activity may contribute to better values of vascular function and autonomic modulation parameters.